Educação básica e extensão universitária: conexões para o desenvolvimento profissional docente - Kohler, Marinéia (2025)
This research investigates university extension at the Federal University of Espírito Santo (Ufes) as a possibility for continuing education and the professional development of basic education teachers. The guiding question of the study is: how can university extension in a public university strengthen the processes of continuing education in the context of the professional development of basic education teachers? The central objective is to understand how the university extension programs offered by the Federal University of Espírito Santo contribute to the continuing education processes of basic education teachers and their professional development. The theoretical framework adopted in this research is based on studies that critically discuss aspects related to teachers' continuing education and university extension, with emphasis on the contributions of Freire (1985, 1996), García (1999), Giroux (1997), Jezine (2006), Lima (2001), and Pimenta (2000, 2006). The research follows a qualitative approach, combining bibliographic and field research, involving two groups: Ufes professors who coordinate extension activities focused on continuing education and basic education teachers who have participated in these initiatives. Data collection was conducted through electronically applied semi-structured questionnaires, and data interpretation followed Bardin’s (2011) content analysis technique. As main results and conclusions, the study indicates that university extension can strengthen teachers' continuing education processes, acting as a mediating dimension between university and school, especially in reinforcing the theory practice unity and encouraging the reconstruction of teaching practices. Among the challenges in this context, the study highlights the need for greater institutional support, increased financial resources, and greater political recognition of extension activities